Villavicencio: From Spontaneous Birth to a Current Intermediary City - Cortés Acuña, Carlos; Castañeda-Pérez, Yonier (Universidad del Rosario, 2020)
The city of Villavicencio has particular characteristics due to its location and its current state, but especially for the territorial configuration from a geo-history of the political economy, due to its relationship with the eastern plains of Colombia, and its close dependence to Bogotá and the Andean area of the country. This article presents a review of the main territorial facts of the formation process of the city from its pre-Hispanic origins in the Guayupe territory to the imposition of the llanera culture in a city populated by Cundiboyacense immigrants and influenced by the colonial haciendas, the phenomena of migration and violence, and the different economic factors that boosted the emergence of an intermediate city with great influence on the national scene.